1976
DOI: 10.1159/000214141
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Coagulation Factors Following Acute Myocardial Infarction in Man

Abstract: The whole blood clotting time, plasma fibrinogen and individual coagulation factors II, V, VII, VIII, IX, X, XI and XII were serially measured in 14 patients over a 10-day period following acute myocardial infarction. A further six patients with similar symptoms but without evidence of myocardial infarction were also studied. The whole blood clotting time was significantly shorter within the first 24 h after infarction than on subsequent days. There were significant increases in the levels of fibrinogen and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] However, the role of FVIII in arterial thrombosis is controversial. In addition, for both venous and arterial thrombosis, it is unclear whether elevated FVIII is merely a proinflammatory biomarker, [14][15][16] a causative mechanism in the disease etiology, or both. We acutely elevated FVIII in mice and examined their susceptibility to thrombosis, and we used ex vivo and in vitro methods to elucidate biochemical mechanisms for the observed effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] However, the role of FVIII in arterial thrombosis is controversial. In addition, for both venous and arterial thrombosis, it is unclear whether elevated FVIII is merely a proinflammatory biomarker, [14][15][16] a causative mechanism in the disease etiology, or both. We acutely elevated FVIII in mice and examined their susceptibility to thrombosis, and we used ex vivo and in vitro methods to elucidate biochemical mechanisms for the observed effects.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] However, associations between FVIII activity and CHD 13 or ischemic heart disease 12 were lost after multivariate adjustment for diabetes and von Willebrand factor (VWF) levels, respectively. Importantly, because FVIII is increased in diseases that induce an acute phase response, including myocardial infarction, 14 surgery, 15 and sepsis, 16 it is unclear whether FVIII's association with either venous or arterial thrombosis simply reflects an ongoing prothrombotic inflammatory process, or whether it is a direct, causative mechanism in the thrombosis etiology and therefore a therapeutic target, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Human coagulation Factor VIII is increased in the circulation under conditions which induce the acute phase response, for example, after surgery (5), in association with a variety of acute and chronic disease states (6,7) or after experimental administration of LPS to volunteers (8). A recent report using IL-6 stimulation of the HepG2 and Chang hepatocyte cell lines as a model system has shown that this increase is at least partially due to an increase in Factor VIII mRNA, but the mechanisms by which this occurs have not yet been defined (9).…”
Section: Introductionmentioning
confidence: 99%
“…4 -11 These side effects are important because of a procoagulant state in acute coronary syndromes. [12][13][14][15][16][17] In patients with AMI and thrombolytic therapy, markedly increased thrombin activation was associated with failure to open the occluded coronary artery and with a high reocclusion rate. 18 As one pathway of thrombin stimulation of thrombolytics, activation of the contact phase of the coagulation by plasmin has been found in vitro.…”
mentioning
confidence: 99%